2021
DOI: 10.29121/granthaalayah.v9.i9.2021.4269
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Financial Distress in Indonesia

Abstract: The results show that, it is proven that the variable liquidity and interest rates have a negative effect on financial distress. Meanwhile, the variables of Profitability, Leverage and Company Size have a positive effect on financial distress. While the Economic Stimulus variable is known to be the relationship between all variables of Liquidity, Profitability, Leverage, Company Size and Interest Rate on variables to Financial Distress. This means that company leaders must take into account liquidity, profitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(2 reference statements)
2
3
0
1
Order By: Relevance
“…Conversely, when the company has a low liquidity ratio, it means that the company's finances are in a bad state and are said to be in an illiquid position (Laksmiwati et al, 2021). A result study conducted by Hastiarto (2021) in manufacturing companies in Indonesia showed that companies would experience lower risks if they had a high percentage level of liquidity, this result is also in line with research by Mesak (2019) and Susdaryo et al, (2021) which showed that liquidity ratios have a significant negative influence on financial distress. However, there are studies that show different results, where the level of liquidity will not affect the risk of companies experiencing financial distress (Arini et al, 2021;Destriwanti et al, 2022;Dirman, 2020).…”
Section: Introductionsupporting
confidence: 70%
“…Conversely, when the company has a low liquidity ratio, it means that the company's finances are in a bad state and are said to be in an illiquid position (Laksmiwati et al, 2021). A result study conducted by Hastiarto (2021) in manufacturing companies in Indonesia showed that companies would experience lower risks if they had a high percentage level of liquidity, this result is also in line with research by Mesak (2019) and Susdaryo et al, (2021) which showed that liquidity ratios have a significant negative influence on financial distress. However, there are studies that show different results, where the level of liquidity will not affect the risk of companies experiencing financial distress (Arini et al, 2021;Destriwanti et al, 2022;Dirman, 2020).…”
Section: Introductionsupporting
confidence: 70%
“…This means that if the intensity of the use of debt in financing a company is greater, then the possibility of financial distress will be even greater. This research is supported by (Susdaryo et al, 2021), which states that in this study states that the leverage variable has a positive effect on financial distress. Based on the results of the regression analysis, the leverage variable shows a positive effect on financial distress.…”
Section: The Effect Of Leverage On Financial Distresssupporting
confidence: 63%
“…According to (Wangsih et al, 2021), that the size of the company which has a significance value of less than 0.05, indicates that partially the size of the company has a significant and negative effect on financial distress in retail trading sub-sector companies listed on the Indonesia Stock Exchange. According to (Susdaryo et al, 2021) in this study states that the company size variable has a negative effect on financial difficulties. Based on the results of regression analysis, the firm size variable does not show a significant effect on the financial distress variable.…”
Section: Effect Of Firm Size Affect To Financial Distressmentioning
confidence: 88%
See 2 more Smart Citations